Mechanistic insights into the structure-dependant and strain-specific utilization of wheat arabinoxylan by Bifidobacterium longum. (1st December 2020) - Song, Ang-Xin; Li, Long-Qing; Yin, Jun-Yi; Chiou, Jia-Chi; Wu, Jian-Yong
Highlights: Ability of Bifidobactera to utilize and metabolize arabinoxylan (AX) for growth was strain specific. The B. longum strain preferred AX or AX hydrolysates with relatively high molecular weight (MW). Both backbone and sidechain structures of AX were recognized for its uptake by B. longum cell. AX was probably partially hydrolyzed extracellularly and further metabolized intracellularly. Abstract: Arabinoxylan (AX), an important dietary fiber from cereal grains, is mainly metabolised in the large intestine by gut bacteria, especially bifidobacteria. This study investigated the uptake and metabolism of wheat AX by a Bifidobacterium longum strain that could grow well with AX as the sole carbon source. The bacterial growth rate showed a significant correlation to the molecular weight (MW) of AX and its acid hydrolysates. Assessment of the key AX degrading enzymes suggested that the uptake and consumption of AX involved extracellular cleavage of xylan backbone and intracellular degradation of both the backbone and the arabinose substitution. The preference for native or partially hydrolysed AX with single substitutions and a sufficiently high MW suggested the structure-dependant uptake by the bacterial cells. Genetic analysis of B. longum showed the lack of β-xylosidase, suggesting the existence of unknown enzymes or dual/multiple-specific enzymes for hydrolysis of the non-reducing end of xylan backbone.